Homelessness and Organ Donor–Derived Bartonella quintana Infection - Rachel Henderson; Emily Mosites; Jane E. Koehler; Carl Boodman; Grace E. Marx (Emerging Infectious Diseases)
Louseborne Bartonella quintana infections in the United States occur almost exclusively among persons experiencing homelessness because of inadequate access to hygiene resources. Homelessness is increasing, and persons experiencing homelessness can be organ donors, despite barriers to receiving donated organs themselves. Recent reports have documented B. quintana transmission via organs transplanted from donors who had recently experienced homelessness. Those reports demonstrate the threat of severe bartonellosis in immunosuppressed organ transplant recipients after donor-derived B. quintana infection. Addressing the root causes of B. quintana transmission could improve the quality of life for persons experiencing homelessness and simultaneously mitigate risk for donor-derived B. quintana transmission. Interventions include improved access to housing, consistent access to hot water for showers and laundry, early treatment of body lice infestation and B. quintana infection, and B. quintana testing and prophylactic treatment of recipients of organs from donors who have experienced risk factors for B. quintana, including homelessness.